MODEL PEMBELAJARAN BERBASIS INTERNET DAN PENGARUHNYA TERHADAP MOTIVASI BERPRESTASI DAN KREATIVITAS BELAJAR SISWA - Idris Harun; Mohd. Fauzan; Muhammad Fitriadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aimed at knowing the influence of internet-based learning model toward students’ achievement motivation and their learning creativity. Quantitative approach was used in this research. Sampling was done by using purposive sampling technique. 300 students at State Islamic Senior High Schools in Riau Province were the samples. Questionnaire was the technique of collecting data. The technique of analyzing data was Linear Regression. The research findings showed that: first, there was a significant influence of internet-based learning model toward student achievement motivation, the correlational score was 0.505 with the significance 0.000 that was lower than 0.05, and R Square score was 0.255, so the contribution of internet-based learning model toward student achievement motivation was 25.5%; second, there was a significant influence of internet-based learning model toward student learning creativity, the correlational score was 0.523 with the significance 0.000 that was lower than 0.05, and R Square score was 0.274, so the contribution of internet-based learning model toward student learning creativity was 27.4%.